231k views
1 vote
Take some time but answer correctly

Take some time but answer correctly-example-1
User Mjswensen
by
5.2k points

2 Answers

1 vote

Answer:

c

Explanation:

Using the rule of exponents


(a^m)^(n) =
a^(mn)

note that 8 = 2³ , then


(8)^(-3)

=
(2^3)^(-3)

=
2^(3(-3))

=
2^(-9) → c

User Brad Axe
by
6.2k points
4 votes

Answer:

c) 2⁻⁹

Explanation:

1) use negative power rule:
x^(-a) =(1)/(x^(a) )

1/2⁹

2) simplify ₂⁹ to 512

1/512 ( same as (8) ⁻3

User Kathe
by
5.8k points